# In the below system, solve for y in the first equation. x - 3y = -6 and 2x - 7y = 10

1/3x + 2, -1/3x + 6, -x + 2, -1/3x + 2

**Solution:**

Given , x - 3y = -6

To solve for y:

Rearrange the terms to isolate y.

x + 6 = 3y

Use the transposing method to solve the equation, we get

y = (x + 6)/3

y = (1/3) x + 2

## In the below system, solve for y in the first equation. x - 3y = -6 and 2x - 7y = 10

**Summary:**

Solving for y in the first equation. x - 3y = -6 and 2x - 7y = 10, we get y = (1/3)x + 2.